Selective increase in specific alternative splice variants of tyrosinase in murine melanomas: A projected basis for immunotherapy - Le Fur, Nathalie (The National Academy of Sciences of the USA, 1997)
Melanomas tend to become less pigmented in the course of malignant progression. Thus, as proliferation increases, the tumors are decreasingly characterized by the tissue-specific phenotype of normally differentiated melanocytes. To learn whether the decline in melanization is associated with a shift from constitutive to alternative splicing of some pigment gene pre-mRNAs, melanomas were collected from Tyr-SV40E transgenic mice of the standard C57BL/6 strain. The mRNAs of the tyrosinase gene, which has a key role in melanogenesis, were analyzed by quantitative reverse transcriptase–PCR in 34 samples from 16 cutaneous tumors and 9 metastases. The cutaneous tumors included some cases with distinct melanotic and amelanotic zones, which were separately analyzed. All tyrosinase transcripts found in the melanomas were also found in normal skin melanocytes. However, the Δ1b and Δ1d alternatively spliced transcripts, due to deletions within the first exon, were specifically augmented in most of the tumors over their very low levels in skin; the exceptions were some all-amelanotic tumors in which no tyrosinase transcripts were detected. The level of Δ1b rose as high as 11.3% of total tyrosinase mRNAs as compared with 0.6% in skin; Δ1d reached 4.0% as compared with 0.8% in skin. Expression of these splice variants was highest in the melanotic components of zonal primary tumors, relatively lower in their amelanotic components, and still lower in all-amelanotic primary tumors and amelanotic metastases. The increase in Δ1b and Δ1d transcripts may be predicted to increase the levels of unusual peptides, which could have antigenic potential in the tumors, especially in the relatively early phases of malignancy. Analyses of the alternative transcripts of other pigment genes may identify additional candidate antigens, ultimately enabling melanoma cells in all phases of the disease to be represented as a basis for immune intervention.